Pengaruh Menghafal Al-Qur'an terhadap Perkembangan Kognitif dan Kemampuan Belajar Anak: Studi Kasus di Rumah Tahfidz Cahaya Surya Sumedang - Parjana, Cepi (IKHBAR: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
This study examines the effects of Quran memorization (tahfidz) on the cognitive development and academic performance of children. A case study was conducted at Rumah Tahfidz Cahaya Surya Sumedang, involving 25 children aged 7.2 years on average, who have been memorizing the Quran for approximately 12 months. The research employed both cognitive tests and academic assessments before and after the tahfidz program to measure the impact on memory, concentration, and academic achievement. The results indicated a significant improvement in short-term memory, verbal recall, and concentration, with a 15% increase in cognitive test scores. Furthermore, 70% of the participants showed an improvement in their academic performance, particularly in subjects requiring high concentration, such as mathematics and language studies. The findings suggest that Quran memorization contributes not only to spiritual development but also to cognitive and academic growth in children.